Stress and Growth in Cancer: Mechanisms and Psychotherapeutic Interventions to Facilitate a Constructive Balance - Ochoa Arnedo, Cristian; Sánchez, Nuria; Sumalla, Enric C.; Casellas-Grau, Anna (Frontiers in Psychology, 2019)
Post-traumatic stress and growth are common responses to adverse life events such as cancer. According to the Janus Face Model proposed by Zoellner and Maercker, the relationship between post-traumatic stress and post-traumatic growth is influenced by illness-related contextual, clinical and therapeutic characteristics. The effect of these post-traumatic responses on adjusting to cancer is potentially determined by the phase of the illness (e.g., initial phases vs. period of survivorship) in addition to the patient’s coping strategies, meaning-making and relationships with significant others. In this article, we establish how cancer becomes a ‘fertile land’ for the emergence of stress and growth processes. We also review the mechanisms of constructive and adaptative stress-growth balances in cancer (oncological process, coping, meaning-making and relational syntony) to study the predictors, interrelated associations, triggering mechanisms, long-term results, and specific trajectories of these two responses to cancer. Finally, we update the evidence on the role of these stress-growth associations in psychologically adjusting to cancer. Together with this evidence, we summarize preliminary results regarding the efficacy of psychotherapeutic interventions that aim to facilitate a constructive psychological balance between stress and growth in cancer patients. Recommendations for future research and gaps in knowledge on stress-growth processes in this illness are also highlighted.